(untitled) (Indian Journal of Animal Production and Management, 2013)
A survey was conducted in 15 villages of Dhemaji district of Assam, comprising 150 non-tribal and 150 tribal households. Both purposive and random sampling methods were used to evaluate performance of indigenous chicken in respect of egg weight, body weight, age at sexual maturity, egg production and hatchability percentage of egg. It was obvious from the results that the body weight of indigenous chicken at day old, 5 months and 10 months of age were not significant (Pd”0.05) between communities. Sexual maturity, egg production per laying cycle and annual egg production were found significantly (Pd”0.05) different between communities except hatchability percentage of egg of indigenous chicken.